Economic institutions of strategy - Nickerson, Jackson A.; Silverman, Brian S. (Emerald, 2009)
Since the publication of Oliver Williamson's Economic Institutions of Capitalism in 1985, new institutional economics approaches have increasingly been used to understand strategic challenges. Economic Institutions of Strategy (EIS) offers an interconnected set of papers that reviews and extends the economic institutional approach to business and corporate strategy bringing together the disparate strands of new institutional economics-based strategy research in a single comprehensive source. The contributors to this volume focus on new institutional economics' insights regarding diversification, alliances, franchising, geographic location, innovation, and other strategic choices. Each contributor uses either a single influential article - with excerpts reprinted - or a survey of the literature to ask and answer three questions: What is the current state of the art in new institutional economics' contribution to fundamental strategic questions? Where has this approach succeeded most, and what gaps remain?.
Keywords: Institutional economics.; Strategic planning.; elektronické knihy; electronic books